Blood pressure and dementia risk by physical frailty in the elderly: a nationwide cohort study - Mi Hee Cho; Kyungdo Han; Seungwoo Lee; Su-Min Jeong; Jung Eun Yoo; SangYun Kim; Jinkook Lee; Sohyun Chun; Dong Wook Shin (Alzheimer’s Research & Therapy, 2023)
Abstract Background Midlife hypertension has been recognized as a modifiable risk factor for dementia, but association between blood pressure (BP) in late life and dementia has been inconclusive. In addition, few studies have investigated effects of BP control on dementia incidence in the frail elderly. Thus, this study aimed to investigate the association of BP and dementia incidence with concomitant consideration of physical frailty in the young elderly population. Methods Using the Korean National Health Information Database, we identified 804,024 subjects without history of dementia at age 66. Dementia diagnosis was defined with prescription records of anti-dementia drugs and dementia-related diagnostic codes. Physical frailty was measured using the Timed Up and Go test. Association of BP and dementia incidence with concomitant consideration of physical frailty was investigated using Cox hazards analyses. Results The risks of Alzheimer’s and vascular dementia increased from systolic BP ≥ 160 and 130–139 mmHg, respectively; a significant association of dementia incidence with low BP was not observed. In the analyses stratified by the physical frailty status, low BP was not associated with increased risks of dementia within the groups both with and without physical frailty. Conclusions High BP was associated with increased risks of dementia, especially for vascular dementia, while low BP was not associated with increased risks of any type of dementia in young elderly people, even in those with physical frailty. This study suggests the need for tight BP control in young elderly people, irrespective of frailty status, to prevent dementia and supports the current clinical guidelines of hypertension treatment.